Teaching Professional Technical Subjects Accepting Current Trends in Field Didactics - Bajtoš Ján; Lajčin Daniel; Gabrhelová Gabriela (Acta Educationis Generalis)
Introduction: In the theoretical study, the authors describe current approaches enriching the theory of field didactics concerning teaching technical subjects. They focus on developing the psychomotor dimension of students’ personalities, which they consider to be an important part of the modern young generation’s culture concept. In order to ensure this role in vocational-technical education, it is necessary to innovate the pedagogical preparation of teachers of technical subjects with a focus on achieving the required teaching competences. A part of the presented study deals with the determination, analysis, and representation of individual teaching competences in the doctoral study plan in the conditions of DTI University in Dubnica nad Váhom, Slovakia.